Enhanced extraction of Synsepalum dulciﬁcum (Miracle Fruit) leaves using green ultrasonication–hydrodistillation method - Nuramira Fateha, Sukor; Rohayu, Jusoh; Nuruldiyanah Syahirah, Kamarudin (Elsevier Ltd, 2020)
In this study, the phenolic compounds of Synsepalum dulcificum leaves were extracted via green sonication-hydrodistillation (UHD) method. The performance of UHD method was compared with conventional hydrodistillation (HD) method with UHD method resulting three-fold higher total phenolic content (TPC) of 124.82 mg GAE/g. The UHD method was further intensified by investigating the effect of extraction temperature ranging from 100 °C to 200 °C. The most intensified temperature was at 120 °C, indicating highest extraction yield of 102.95 mg/g. Different mathematical models namely rate law, Peleg's model and Fick's model were analysed and it was found that Fick's model was successfully predict the UHD process which confirms that diffusivity is the controlling factor in extracting phenolic compounds, instead of the capacity and the rate of reaction as proposed by Peleg's model and rate law, respectively. Hence, it can be concluded that UHD method effectively enhanced the extraction efficiency to increase the extraction yield of phenolic compounds in S. dulcificum leaves.